Pengaruh Social Media Marketing dan Inovasi Produk Terhadap Keputusan Pembelian Di UMKM Jahe Mbah Jayus Malang - Zafirah, Deandra; Nurtjahjani, Fullchis; Maskan, Mohammad (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research was an explanatory study with a quantitative approach, using variables of social media marketing, product innovation, and purchasing decisions. This study used observation and questionnaire data collection techniques. With a purposive sampling technique, 100 respondents were obtained as consumers and followers of the @jahembahjayus Instagram account. The data analysis methods employed in this study included multiple linear regression and hypothesis testing. The results indicated that social media marketing and product innovation positively and significantly impacted purchasing decisions.